Bioassay-guided isolation of a vasorelaxant active compound from Kaempferia galanga L. - Othman, Rozana; Ibrahim, Halijah; Mohd, Mustafa Ali; Mustafa, Mohd Rais; Awang, Khalijah (Elsevier, 2006)
Bioassay-guided fractionation was performed on a crude dichloromethane extract of Kaempferia galanga L. using chromatography techniques. Screening of the extract for biological activity started with the brine shrimp lethality bioassay, followed by the study of its antihypertensive activity on anaesthetized rats, which involved monitoring of the extract's effect on mean arterial blood pressure. The components of the fractions obtained from the separation procedures were analyzed using gas chromatography (GC). The yield of the CH2Cl2 extract was 0.29% of the crude plant extract. Analysis of the data for brine shrimp lethality test using the Finney computer program showed that this extract exhibited potent bioactivity with an ED50 value of 7.92±0.13 μg ml−1. Intravenous administration of the extract induced a dose-related reduction of basal mean arterial pressure (MAP) (130±5 mmHg) in the anaesthetized rat, with maximal effects seen after 5–10 min of injection. The gas chromatogram showed that the common compound in the active fractions obtained from the bioassay-guided fractionation of the CH2Cl2 extract was ethyl cinnamate. This vasorelaxant active compound, ethyl cinnamate, was isolated as a colorless oil. Ethyl p-methoxycinnamic acid was also isolated as white needles but did not exhibit any relaxant effect on the precontracted thoracic rat aorta.